Comparison of Extraction Techniques for the Determination of Volatile Organic Compounds in Liverwort Samples - Małgorzata Guzowska; Wiesław Wasiak; Rafał Wawrzyniak (Molecules, 2022)
This article focuses on the comparison of four popular techniques for the extraction of volatile organic compounds (VOCs) from liverworts of the Calypogeia azurea species. Since extraction is the most important step in the sample analysis of ingredients present in botanical preparations, their strengths, and weaknesses are discussed. In order to determine the VOCs present in plants, selecting the appropriate one is a key step of the extraction technique. Extraction should ensure the isolation of all components present in the oily bodies of Calypogeia azurea without the formation of any artifacts during treatment. The best extraction method should yield the determined compounds in detectable amounts. Hydrodistillation (HD), applying Deryng apparatus and solid-liquid extraction (SLE), microwave-assisted extraction (MAE), and headspace solid-phase microextraction (HS-SPME) were used for volatile extraction. The extracts obtained were analysed by gas chromatography coupled to mass spectrometry (GC-MS) to determine the compounds.